THE ROLE OF PROFESSIONAL IDENTITY IN IMPROVING NURSING SERVICE QUALITY AND JOB SATISFACTION: A LITERATURE REVIEW - Saputra, Dikki; Nabilla, Putri; Intani, Merlisa Kesuma; Fauzan, Suhaimi (Jurnal Keperawatan dan Kesehatan, 2025)
Professional identity reflects how nurses perceive and evaluate themselves, shaped by the values, norms, and ethical principles of the nursing profession. This concept encompasses four key aspects: professional values, ethics, knowledge, and leadership. Professional identity contributes to the quality of nursing care and nurses' job satisfaction. This study aims to explore the role of professional identity in these two aspects. A descriptive literature review was conducted to examine the relationship between professional identity, quality of care, and job satisfaction. Following JBI guidelines, the review evaluates nurses’ knowledge, motivation, and practices related to discharge planning. Searches were conducted in PubMed, ScienceDirect, and ProQuest using the keywords "Professional Identity" AND "Nurses," "Quality of Care," AND "Job Satisfaction," focusing on articles from 2019-2024. Results reveal a significant link between professional identity and job satisfaction, with professional identity also influencing burnout potential. Self-directed learning serves as a mediator, while a supportive work environment and positive organizational climate enhance nurse engagement and job satisfaction. A strong professional identity leads to better care quality and job satisfaction, with nurses gaining a clearer understanding of their roles.